2018
DOI: 10.2345/0899-8205-52.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Review : Use of Simulation-Based Training to Aid in Implementing Complex Health Technology

Abstract: Clinicians are adult learners in a complex environment that historically does not invest in training in a way that is conducive to these types of learners. Adult learners are independent, self-directed, and goal oriented. In today's fast-paced clinical setting, a practical need exists for nurses and clinicians to master the technology they use on a daily basis, especially as medical devices have become more interconnected and complex. As hospitals look to embrace new technologies, medical device companies must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was concluded that online simulation training provides a virtual hands-on experience in advance of implementing new equipment and coupled with adult learning principles, may enhance the experience of clinical end users of technology. Especially in home environment, augmented technology will add skills to manage safety hazards [6].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that online simulation training provides a virtual hands-on experience in advance of implementing new equipment and coupled with adult learning principles, may enhance the experience of clinical end users of technology. Especially in home environment, augmented technology will add skills to manage safety hazards [6].…”
Section: Resultsmentioning
confidence: 99%
“…Advanced teaching equipment was an essential tool for training students who would become medical personnel in the future [ 54 ]. Modern technologies such as multimedia, teaching simulation facilities, and virtual simulation facilities provided students with a virtual “hands-on” experience [ 55 , 56 ], which would stimulate their professional interest and improve their professional satisfaction. Second, the number of study rooms was positively related to student satisfaction [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we need to think about initial training that is standard across the board, then it's a matter of leveraging your internal resources to adapt competencies to fit the workflow for each department in addition to the standard rollouts, while considering adult-learning principles. 2 Those principles involve being able to see, hear, and touch the device, as well as the ability for end users to demonstrate that they actually understand what they're seeing, hearing, and touching and can incorporate the new device and workflow into their practice effectively.…”
Section: Competency Process For Complex Technologymentioning
confidence: 99%